Unsupervised Chunking Based on Graph Propagation from Bilingual Corpus. (19th March 2014) - Zhu, Ling; Wong, Derek F.; Chao, Lidia S.
Abstract : This paper presents a novel approach for unsupervised shallow parsing model trained on the unannotated Chinese text of parallel Chinese-English corpus. In this approach, no information of the Chinese side is applied. The exploitation of graph-based label propagation for bilingual knowledge transfer, along with an application of using the projected labels as features in unsupervised model, contributes to a better performance. The experimental comparisons with the state-of-the-art algorithms show that the proposed approach is able to achieve impressive higher accuracy in terms of F -score.